Description of the larva of a firefly species, Pygoluciola dunguna Nada (Coleoptera: Lampyridae) - Nada, B.; Ballantyne, L. A.; Jusoh, Wan F. A. (Zootaxa, 2021)
Pygoluciola dunguna Nada, 2018 was described from Peninsular Malaysia, using males and reliably associated females. This paper details description of the larva which has been conclusively identified as Pygoluciola dunguna based on DNA barcoding technique and uses morphology, brief habitat and behavioural data. A total of 70 larval specimens were measured and their main features described. The larvae exhibit a riparian or semi-aquatic behaviour, observed crawling on the sandy edge of shallow streams. The stake-like projections along the length of the body suggest a form of defensive mechanism from falling prey to aquatic predators.